The Radiocarbon Record of the Western Stemmed Tradition on the Southern Columbia Plateau of Western North America. Issue 3 (July 2019) - Brown, Thomas J.; Gilmour, Daniel M.; Solimano, Paul S.; Ames, Kenneth M.
Abstract : The late Pleistocene–early Holocene archaeological record of the interior Pacific Northwest is dominated by what has been regionally referred to as the Western Stemmed Tradition (WST). While various efforts have attempted to clarify the chronology of this tradition, these have largely focused on data from the Great Basin and have been disproportionately preoccupied with establishing the beginning of the tradition due to its temporal overlap with Clovis materials. Specifically focusing on the Columbia Plateau, we apply a series of Bayesian chronological models to create concise estimates of the most likely beginning, end, and span of the WST. We then further explore its chronology by modeling its temporal span under various parameters and criteria so as to better identify places in the chronology that need further work and those that are robust regardless of data iteration. Our analysis revealed four major findings: (1) WST conservatively dates between 13, 000 and 11, 000 cal BP, likely extending to ~13, 500 cal BP; (2) the most problematic period for WST is its termination; (3) the WST is incredibly long-lived compared to roughly contemporary Paleoindian traditions; and (4) the WST was seemingly unaffected by the onset of the Younger Dryas. Abstract : El registro arqueológico del Pleistoceno Tardío/Holoceno Temprano del sector interior del Noroeste Pacífico (Pacific Northwest) está dominado por lo que ha sido regionalmente denominado como la Tradición Pedunculada Occidental (Western Stemmed Tradition, WST). Se ha trabajado mucho buscando clarificar la cronología de esta tradición, pero enfocando el análisis en la Gran Cuenca y ocupándose desigualmente de los comienzos de la misma, debido a su superposición temporal con materiales Clovis. Enfocándonos específicamente en la Meseta Columbia aplicamos una serie de modelos cronológicos Bayesianos para crear estimaciones concisas del más probable comienzo, final y vigencia de la WST. Posteriormente exploramos su cronología modelando su tiempo de vigencia bajo varios parámetros y criterios, a fin de identificar mejor los sectores de la cronología que necesitan más trabajo y aquellos que son robustos independientemente de la iteración de datos. Nuestro análisis reveló cuatro hallazgos principales: (i) la WST se puede datar en forma conservadora dentro del lapso 13, 00-11, 000 cal AP, probablemente extendiéndose a ~13, 500 cal AP (ii) el período más problemático para la WST es su finalización (iii) la WST es increíblemente duradera en comparación con las tradiciones Paleoindias aproximadamente contemporáneas y (iv) la WST aparentemente no fue afectada por el inicio de del Younger Dryas.